Pre- and post-weaning injections of bovine somatotropin to optimize puberty achievement of Bos indicus beef heifers - Moriel, Philipe; Cappellozza, Bruno Ieda; Piccolo, Matheus B.; Cooke, Reinaldo F.; Miranda, Miguel F. [UNESP]; Batista, Luis F. D. [UNESP]; Carvalho, Rafael S. [UNESP]; Colombo, Eduardo A. [UNESP]; Santili, Felipe [UNESP]; Filho, Ramiro V. O. [UNESP]; Ferreira, Vitor S. M. [UNESP]; Vasconcelos, Jose L. M. [UNESP] (Oxford Univ Press Inc, 2019)
The present study evaluated the growth and puberty attainment of Bos indicus heifers administered recombinant bovine somatotropin (bST) or saline injections during preweaning and/or postweaning. On day 0, 177 suckling Nellore heifers were stratified by initial age and body weight (BW) (80 +/- 10 d; 97 +/- 16 kg), and randomly assigned, in a 2 x 2 factorial design (n = 44 to 45 heifers/treatment), to receive s.c. injections of saline (5 mL 0.9% NaCl) or sometribove zinc (Posilac; Elanco, Greenfield, IN; 6.14 mg/kg of BW0.75) on days 0 and 10 (PRE) and/or days 167 and 177 (POS). All heifers were managed as a single group in Brachiaria decumbens pastures from day 0 until 24 d postweaning (day 191), and then provided a corn silage-based TMR from days 191 to 380 to achieve 65% to 70% of mature BW at the end of the study (day 380). Heifer full BW was collected on days 0, 10, 167, 177, and monthly from days 191 to 380. Transrectal ultrasonography of ovaries was performed on days 1 and 10 of each month from days 229 to 380 to assess the percentage of pubertal heifers. Liver biopsies and blood samples from jugular vein were collected on days 0, 10, 167, 177, and 380. Additional blood samples were collected monthly from days 259 to 380 (n = 10 to 15 heifers/treatment). No interactions among day of the study, PRE, and POS injections of saline or bST were detected (P = 0.11). Preweaning bST injections increased heifer average daily gain (ADG) from days 0 to 10 and plasma IGF-1 on day 10 (P <= 0.03), did not affect ADG from days 0 to 177, plasma IGF-1 from days 259 to 380, and any liver gene mRNA expression (P >= 0.19), but tended to decrease ADG from days 191 to 380 (P = 0.07) and percentage of pubertal heifers on days 349 (P = 0.07), 359 (P = 0.002), and 380 (P = 0.0001) compared with saline injections. Postweaning bST injections increased plasma IGF-1 on day 177 and overall liver mRNA expression of GHR-1A (P <= 0.05), decreased plasma IGF-1 from days 259 to 380 (P = 0.03), tended to decrease liver mRNA expression of GHR-1B on day 177 (P = 0.08), but did not affect ADG from days 167 to 177 and 191 to 380, and puberty attainment from days 229 to 380 (P >= 0.12) compared with saline injections. Thus, preweaning and postweaning injections of bST successfully increased heifer plasma IGF-1 concentrations 10 d after first injection. Postweaning injections of bST had no impact on puberty attainment, whereas preweaning bST injections of bST impaired puberty attainment of Nellore beef heifers.
Keywords: beef heifers; Bos indicus; insulin-like growth factor 1; metabolic imprinting; puberty; somatotropin